ChemInform Abstract: Herbicidal Ionic Liquids Based on Esterquats. Issue 36 (September 2015) - Pernak, Juliusz; Czerniak, Kamil; Niemczak, Michal; Chrzanowski, Lukasz; Lawniczak, Lukasz; Fochtman, Przemyslaw; Marcinkowska, Katarzyna; Praczyk, Tadeusz
Abstract Novel herbicidal ionic liquids (HILs) containing different anions and cations derived from ammonium esterquats are prepared by employing a simple, inexpensive pathway.